2021
DOI: 10.5334/irsp.503
|View full text |Cite
|
Sign up to set email alerts
|

These Are Not Just Words: A Cross-National Comparative Study of the Content of Political Apologies

Abstract: Was it enough merely to say "sorry" on the part of those who had the humility, courage and honesty to say "sorry"? And what of those who are perhaps too arrogant to utter this simple word?' 1 In his speech at the commemoration of the Rwandan genocide in April 2004, South African President Mbeki questions the relevance of offering an apology when such a heinous crime has happened. After himself apologizing for South Africa's passivity and highlighting the inaction of the international community during the 1994 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For example, Kirchhoff and Cehajic-Clancy (2014) examined which components a ‘good’ apology needs to include, but their studies yielded inconsistent results as to which elements are most essential for an apology to be ‘effective’. In their analysis of the content of state apologies across the world, Zoodsma et al (2021, but see also Zoodsma and Schaafsma, 2022) also observed that many of these statements only contain a selection of the components that are deemed essential in the literature, and they proposed a more liberal set of criteria to identify state apologies. For example, they included in their political apology database all statements by political authorities that included words such as ‘sorry’, ‘apologize’, and expressions of regret or remorse, or requests for forgiveness, but they also included statements that included expressions of guilt or shame if this was also accompanied by an acknowledgment of past wrongdoing.…”
Section: Distinguishing Between State Apologies and Non-apologiesmentioning
confidence: 99%
“…For example, Kirchhoff and Cehajic-Clancy (2014) examined which components a ‘good’ apology needs to include, but their studies yielded inconsistent results as to which elements are most essential for an apology to be ‘effective’. In their analysis of the content of state apologies across the world, Zoodsma et al (2021, but see also Zoodsma and Schaafsma, 2022) also observed that many of these statements only contain a selection of the components that are deemed essential in the literature, and they proposed a more liberal set of criteria to identify state apologies. For example, they included in their political apology database all statements by political authorities that included words such as ‘sorry’, ‘apologize’, and expressions of regret or remorse, or requests for forgiveness, but they also included statements that included expressions of guilt or shame if this was also accompanied by an acknowledgment of past wrongdoing.…”
Section: Distinguishing Between State Apologies and Non-apologiesmentioning
confidence: 99%
“…Worldwide history abounds with examples of political apologies (MacLachlan, 2010). In recent years, there is a consistently increasing number of political apologies following historical wrongdoings and injustices in a historical, national and political level (Celermajer, 2009;Gibney, 2008;Zoodsma et al, 2021). To this end, politicians seem to face past wrongdoings and injustices by making morally-based amends for such wrongs (Howard-Hassmann & Gibney, 2008).…”
mentioning
confidence: 99%
“…a recognition of wrongdoing, a recognition of suffering) were included. More details can be found in Zoodsma et al (2021).…”
mentioning
confidence: 99%